Upstream open reading frames (uORFs) as translational regulators in human disease - Fernandes, Rafael (2020)
The messenger RNA (mRNA) translation process is a key step of gene expression, whose regulation allows the cell to rapidly change protein synthesis in a spatio-temporal manner in response to different stimuli. Translation comprises four steps – initiation, elongation, termination, and ribosome recycling – being initiation the rate-limiting step that is, therefore, prone to a tighter regulation. Among the regulatory elements and factors that can act in this stage, there are the upstream open reading frames (uORFs), which represent coding regions defined by an initiation codon in the 5’ leader sequence [also known as 5’ untranslated region (UTR)] of the mRNAs, in frame with an upstream termination codon or overlapped with the main open reading frame (mORF) that encodes the protein. These cis-acting elements are typically considered to be repressors of downstream translation in basal conditions since they may function as “barriers” to ribosomes, impeding them to reach the mORF.